Unmet need in Sierra Leone: a national oral health survey of schoolchildren - S. G. Ghotane; S. J. Challacombe; P. Don-Davis; D. Kamara; J. E. Gallagher (Nature Publishing Group, 2022)
Abstract Objective Sierra Leone (SL), in West Africa, with a population of over 7.5 million people has suffered the effects of a civil war previously, and more recently Ebola & Covid-19. Dental care is very limited, mostly in the capital Freetown and the private sector. No dental education is available in the country. The objective of this research was to investigate the oral health needs of schoolchildren at key ages, to inform future action. Materials and methods This first national oral health survey of schoolchildren at 6-, 12- and 15-years was conducted in urban and rural settings across all four regions using a multi-stage cluster sampling in line with the WHO guidelines, adapted according to contemporary survey methods to include 'International Caries Detection and Assessment System (ICDAS)'. Whilst parents were invited to complete a questionnaire for 6-year-old children, 12- and 15-year-olds self-completed a questionnaire. Data were weighted according to age and regional population and analysed using STATA v.15 and SPSS v.22. Results A total of 1174 children participated across 22 schools from all four regions. Dental caries was prevalent (over 80% of all age-groups having clinical decay; ICDAS score ≥ 2) and largely untreated. No children had fillings and only 4% had missing teeth. Amongst 6, 12 and 15-year-olds, average decay levels at ICDAS > 3 threshold was 3.47 (primary teeth), 2.94 and 4.30 respectively. Almost, 10% (n = 119) of all children reported experiencing pain in their teeth with 7% (n = 86) children having PUFA lesions present. At least one in five children required one or more dental extractions. 'Age' was a significant predictor of dental caries experience and the odds of having dental caries experience was higher in rural areas at D3-6MFT (p < 0.05). Conclusion The findings demonstrate a vast unmet oral health need in the children of SL. Using ICDAS as an epidemiological tool in a low-income country provides valuable insight to the pattern of oral disease to inform health service planning. Urgent action is required to address this silent epidemic.